Interventions sur les secteurs dégradés Cas de la médina de Constantine « Quartier de Sidi Djeliss » - HAMMAR, Nassima Tassadit; Mr. ALIKHODJA Nadir (Encadreur); Mme. BOUSNINA Monia (Co-Encadreur) (Université Ferhat Abbas Sétif 1. Institut d'architecture et sciences de la terre. Département d'architecture, 2015)
Today our cultural architectural heritage is a fragile and threatened complex reality, which now has an important role in the life and development of our societies ; this awareness of the dangers threatening this heritage encourages us to preserve it in order to transmit it in good conditions to the future generations. The main objective of our work is to revive the neighborhood of Sidi Djeliss, which is in a degraded area. Our first task was to study the medina of Constantine, its history, its characteristics and its specificities. Then urban district analysis and diagnosis of the current situation helped us to propose the actions necessary for the enhancement of the most important constructions, but also the protection of intangible cultural property. The program is developed around the creation of a "House of Memory and Heritage" that will have for mission the safeguarding, transmission and teaching of Constantine cultural architectural heritage. In the final, in the words of Guido Canali, "the goal it is not to hurt the past architecture but to give him the opportunity to show its best in the company of contemporary architecture".
التراث اليوم هو واقع معقد، هش و مهدد، و لديه دورا هاما في حياة و تطور المجتمعات، و وعينا بالمخاطر التي تهدد هذا التراث، يشجعنا على الحفاظ عليه , لنقله الى الأجيال القادمة. الذي يقع في منطقة متدهورة. » سيدي جليس « الهدف الرئيسي لعملنا، هو احياء حي المهمة الأولى هي دراسة مدينة قسنطينة تاريخها، خصائصها وخصوصياتها. وبعدها التحليل الحضري للحي وتشخيص الوضع الراهن للمنطقة هما العاملان المساعدان على اقتراح الإجراءات اللازمة لتعزيز التراث المبني، ولكن أيضا حماية الممتلكات الثقافية غير المادية بهدف حماية، نقل وتدريس التراث الثقافي القسنطيني. » دار الذاكرة والتراث « ثم تطور هذا البرنامج من خلال انشاء لا يتمثل الامر في إيذاء الهندسة المعمارية القديمة، ولكن إعطائها فرصة لظهور في أحسن ايامها كهندسة معمارية « : وأخيرا كما قال كنالي جويدو معاصرة.
Keywords: Patrimoine; Médina; Secteur dégradé; Bien Culturel Immatériel; Rénovation; Réhabilitation